Longitudinal Clinical Profiles of Hospital vs. Community-Acquired Acute Kidney Injury in COVID-19 - Lu, Justin Y.; Babatsikos, Ioannis; Fisher, Molly C.; Hou, Wei; Duong, Tim Q. (Frontiers in Medicine, 2021)
Acute kidney injury (AKI) is associated with high likelihood of critical illness and mortality in COVID-19 patients. It is unclear however whether COVID-19 patients with hospital-acquired AKI (HAKI) and community-acquired AKI (CAKI) differ in disease course and outcome. This study investigated the clinical profiles of HAKI, CAKI, and non-AKI COVID-19 patients. Of the hospitalized COVID-19 patients (N=1324), 23.26% had HAKI, 22.28% had CAKI, and 54.46% had no AKI. HAKI patients were older and had more comorbidities than CAKI and non-AKI patients (p<0.05). HAKI cohort had higher prevalence of coronary artery disease, heart failure, and chronic kidney disease than CAKI cohort (p<0.05). HAKI had higher mortality than NAKI (adjusted OR: 4.67 [95%CI:3.1,7.0], p<.001), and more than CAKI (adjusted OR: 1.61 [95%CI:1.1,2.35], p<0.014). CAKI had higher mortality than NAKI (adjusted OR: 3.39 [95%CI:2.2, 5.21], p<0.001). Although laboratory tests known to be associated with poor outcomes of CAKI patients were abnormal compared to non-AKI patients, they were not as abnormal compared to HAKI patients. HAKI and CAKI COVID-19 patients received more invasive and non-invasive mechanical ventilation, prophylactic and therapeutic anticoagulants, steroids and dialysis than non-AKI patients (p<0.05). Notably, CAKI patients had markedly lower prevalence of liver injury in contrast to HAKI patients (p<0.05). These results together suggest that HAKI is likely part of systemic multi-organ damage, and that kidney injury per se contributes to worse outcomes but does not appear to be the main cause of worse outcomes. These findings provide insights that could lead to better management of COVID-19 patients in time-sensitive and potentially resource-constrained environments.